KHOJA AHROR VALIU IS ABOUT RECONCILIATION IN BUILDING AN ENLIGHTENED SOCIETY THE IMPORTANCE OF THEIR VIEWS (Scientific journal of the Fergana State University, 2024)
The article states that self-awareness of a person is the basis of perfection, that a person should understand himself in order to be in harmony with himself and others, Khoja Ahror Vali's basic philosophy of compromise is to protect the soul from the desires, to stay away from bad interlocutors, and good interlocutors are important for human perfection. The importance of these ideas for the education of a mature generation has been reflected. The importance of Khoja Ahror Vali's ideas on reconciliation in building an enlightened society is explained in detail.